Liposomal delivery of dexamethasone attenuates prostate cancer bone metastatic tumor growth In Vivo. Issue 8 (8th February 2015) - Kroon, Jan; Buijs, Jeroen T.; van der Horst, Geertje; Cheung, Henry; van der Mark, Maaike; van Bloois, Louis; Rizzo, Larissa Y.; Lammers, Twan; Pelger, Rob C.; Storm, Gert; van der Pluijm, Gabri; Metselaar, Josbert M.
<x xml:space="preserve">Abstract</x> Background The inflammatory tumor microenvironment, and more specifically the tumor‐associated macrophages, plays an essential role in the development and progression of prostate cancer towards metastatic bone disease. Tumors are often characterized by a leaky vasculature, which ‐ combined with the prolonged circulation kinetics of liposomes ‐ leads to efficient tumor localization of these drug carriers, via the so‐called enhanced permeability and retention (EPR) ‐effect. In this study, we evaluated the utility of targeted, liposomal drug delivery of the glucocorticoid dexamethasone in a model of prostate cancer bone metastases. Methods Tumor‐bearing Balb‐c nu/nu mice were treated intravenously with 0.2–1.0–5.0 mg/kg/week free‐ and liposomal DEX for 3–4 weeks and tumor growth was monitored by bioluminescent imaging. Results Intravenously administered liposomes localize efficiently to bone metastases in vivo and treatment of established bone metastases with (liposomal) dexamethasone resulted in a significant inhibition of tumor growth up to 26 days after initiation of treatment. Furthermore, 1.0 mg/kg liposomal dexamethasone significantly outperformed 1.0 mg/kg free dexamethasone, and was found to be well‐tolerated at clinically‐relevant dosages that display potent anti‐tumor efficacy. Conclusions Liposomal delivery of the glucocorticoid dexamethasone inhibits the growth of malignant bone lesions. We believe that liposomal encapsulation of dexamethasone offers a promising new treatment option for advanced, metastatic prostate cancer which supports further clinical evaluation. Prostate 75: 815–824, 2015. © 2015 The Authors. The Prostate, published by Wiley Periodicals, Inc.